165 A retrospective study showing the safety of minimally invasive surgery of cervical cancer. (18th September 2019) - Ditto, A; Leone Roberti Maggiore, U; Martinelli, F; Bogani, G; Evangelista, MT; Chiappa, V; Murgia, F; Sonetto, C; Maltese, G; Zanaboni, F; Raspagliesi, F; Raspagliesi, F
Abstract : Objectives: Cervical cancer (CC) is the fourth most common malignancy in women worldwide. Surgical treatment, including radical hysterectomy and pelvic ± para-aortic lymphadenectomy, is the gold standard for women with early stage CC. Recently, the LACC trial demonstrated that minimally invasive surgery was associated with lower rates of disease-free survival (DFS) and overall survival (OS) than open surgery among women with early-stage CC. The aim of the current study was to present our experience with laparoscopic treatment of patients with CC in terms of OS and DFS as well as the type and site of recurrence. Methods: This was a retrospective analysis of a prospectively collected database of patients with CC who underwent laparoscopic surgery. The primary outcome of this study was to evaluate the 5-year OS and DFS. Secondary outcome was to compare the rate and the type of recurrences rate. Results: Ninety-one patients were included in this study. All patients underwent laparoscopic radical treatment; no conversion was required. DFS was 33.7±27.2 months. A total of 10 patients (11.0%) had recurrence diagnosed during follow-up. Site of recurrence were: pelvis in 6 cases (6.0%), lymph node in one case (1.0%), lung in two cases (2.0%) and both pleural and pelvis in 1 case (1.0%). Time to recurrence among patient who had recurrence was 14.4±10.8 months. OS was 32.5±27.1 months. Conclusions: Although we acknowledge the limitations of the study design, this retrospective series demonstrated the safety of laparoscopic radical treatment of patients with CC as demonstrated by the low rate of recurrence.